The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21577/0103-5053.20180131
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Fingerprinting and Profiling of the Medicinal Grass Eleusine indica Based on HPLC-DAD, UPLC-DAD-MS/MS and NMR Analyses

Abstract: Aqueous preparations of the grass Eleusine indica are used for treating malaria and lung infections. Despite its widespread occurrence and therapeutic potential, little is known about its chemical composition. This study reports a common chemical pattern for aqueous extracts of E. indica samples from four different localities, separated from each other by approximately 75 to 1340 km, in a wide variety of abiotic and biotic factors. High-performance liquid chromatography with diode array detection (HPLC-DAD), u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Among the flavonoids, schaftoside (C-glycosyl-6-C-arabinosyl-8 apigenin) and vitexin (apigenin-8-C-glucoside) have been isolated from aerial parts [14] . P-Coumaric acid and isoschaftoside have also been identified in the herbal medicine [26] . The compounds isolated from the organs of E. indica are summarized in Table 1: Aerial parts Lyophilized extract Isoschaftoside [26] Aerial parts Lyophilized extract acid p-coumarique [26] Aerial parts Lyophilized extract Vitexine [26] Aerial parts Hexane extract 1 -[[[(2-aminoethoxy) hydroxyphosphinyl]oxy]methyl]1-,2-ethandiylester [27] Aerial parts Methanol extract Acide hexadecanoique [27] Leave Essential oil Heptacosane [28] Leave Essential oil Pentatriacotene [28] Leave Essential oil Docosanol [28] Leave Essential oil 2-methylhexan-1-ol [28] Leave Essential oil Nonadecane [28] Leave Essential oil Cis-13-eicosenique [28] Leave Essential oil 2,6,10-trimethyltetradecane [28] Leave Essential oil Tert-hexadecanethiol [28] Leave Essential oil Nonadocane [28]…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…Among the flavonoids, schaftoside (C-glycosyl-6-C-arabinosyl-8 apigenin) and vitexin (apigenin-8-C-glucoside) have been isolated from aerial parts [14] . P-Coumaric acid and isoschaftoside have also been identified in the herbal medicine [26] . The compounds isolated from the organs of E. indica are summarized in Table 1: Aerial parts Lyophilized extract Isoschaftoside [26] Aerial parts Lyophilized extract acid p-coumarique [26] Aerial parts Lyophilized extract Vitexine [26] Aerial parts Hexane extract 1 -[[[(2-aminoethoxy) hydroxyphosphinyl]oxy]methyl]1-,2-ethandiylester [27] Aerial parts Methanol extract Acide hexadecanoique [27] Leave Essential oil Heptacosane [28] Leave Essential oil Pentatriacotene [28] Leave Essential oil Docosanol [28] Leave Essential oil 2-methylhexan-1-ol [28] Leave Essential oil Nonadecane [28] Leave Essential oil Cis-13-eicosenique [28] Leave Essential oil 2,6,10-trimethyltetradecane [28] Leave Essential oil Tert-hexadecanethiol [28] Leave Essential oil Nonadocane [28]…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…A study by Penaloza et al in 2018 using NMR spectroscopy reported that the aerial parts of E. indica contained four specific compounds-flavonoids schaftoside, isoschaftoside, vitexin, and p-coumaric acid. 9 They have also detected 29 unknown compounds which they grouped into fatty acid derivatives, amino acids, carbohydrates, and aromatics. 9 Among all these components, flavonoids, p-coumaric acid, and fatty acid derivatives have the potential to promote the inhibition of the P. aeruginosa quorum-sensing network.…”
Section: Quorum Sensing Inhibition Assay Against P Aeruginosamentioning
confidence: 99%
“…9 They have also detected 29 unknown compounds which they grouped into fatty acid derivatives, amino acids, carbohydrates, and aromatics. 9 Among all these components, flavonoids, p-coumaric acid, and fatty acid derivatives have the potential to promote the inhibition of the P. aeruginosa quorum-sensing network. A few plants, such as Centella asiatica L. and Psidium guajava L., which have been shown to inhibit the swarming motility of P. aeruginosa in a dose-dependent manner, have been reported to contain rich amounts of flavonoids, including kaempferol, quercetin, apigenin, rutin, and naringin.…”
Section: Quorum Sensing Inhibition Assay Against P Aeruginosamentioning
confidence: 99%
See 1 more Smart Citation
“…The antidiabetic activity of ethanolic leaf extract of E. indica was investigated in a model of alloxan-induced diabetes in rats which showed that there are reduced blood glucose levels [ 26 ]. On the other hand, in Brazil, aqueous preparations of the grass E. indica are used for treating malaria and lung infections [ 27 ]. In Malaysia, E. indica is traditionally used in ailments associated with the liver and kidneys [ 28 ].…”
Section: Introductionmentioning
confidence: 99%